The Role of Implementation of Service Management and Security Frameworks in Information Technology Service Continuity - Soheila Jafarnezhad; Mohammad Reza Taghva (مطالعات مدیریت کسب و کار هوشمند, 2019)
Competitive business environment and high dependency to the services has caused organizations to be evaluated based on the level of their ability in providing continuous services. Information Technology (IT) service continuity management discusses the capabilities of the organization to maintain an acceptable and predetermined level of IT services to support business requirements in the event of an incident. Information security management, while minimizing disruptions to business and IT Infrastructure Library (ITIL), is an appropriate structure for organizations that deliver IT services to their customers with the aim of supporting business processes. The aim of this study is to identify factors affecting the continuity of IT services. After a thorough literature review, a questionnaire was prepared using a five-point Likert scale and handed to 8 experts. The questionnaire was verified by experts in the field and then was sent to 60 IT experts of the organizations and companies. After analyzing the results, the identified factors were confirmed and the main research hypothesis - the impact of the implementation of the ITIL and the information security management system on the continuity of the IT services- was confirmed.